REVIEW OF VICTIMOLOGY OF VICTIMS OF THEFT IN THE CRIMINAL JUSTICE SYSTEM - Rhendy Ahmad Fauzi (Jurnal Ilmiah Advokasi, 2023)
Victimology, from the word victim (victim) and logi (science), Latin victima (victim) and logos (science). In simple terms, victimology means the science of victims (crimes). According to the Crime Dictionary, which is quoted by an Abussalam expert, the victim is "a person who has suffered physical or mental suffering, lost between objects or resulted in death for acts or attempts of minor offenses committed by criminals and others". Here it is clear that "people who suffer physical suffering and so on" are victims of violations or criminal acts.In conducting research in order to be carried out optimally, the researchers used several methods, in this study using a normative juridical approach. Normative juridical, namely the study of legal principles, legal systematics, level of legal synchronization and legal comparisons. This normative juridical is an effort to inventory positive law. In this approach method examines legal issues based on normative rules whether in accordance with social life. To obtain the data and information referred to by this thesis, the author uses the nature of descriptive analysis research.The crime of theft is a criminal act, which greatly disturbs the comfort of the people. For that we need a consistent action that can enforce the law, so that harmony is established. As it is known that Law Number 8 of 1981 concerning the Criminal Procedure Code adheres to a criminal justice system that prioritizes the protection of human rights, but if the provisions regarding this matter are considered more deeply, it turns out that only the rights of the suspect/defendant are much highlighted while the rights of victims of theft. In line with this principle, the public, especially the mass media, focus more on the rights of the suspect/defendant rather than questioning the protection of victims of theft.Keywords: Victimology, Theft, Criminal Justice System